EXPLORING PEER COOPERATIVE LEARNING THROUGH INDEX CARD MATCH IN ENGLISH LANGUAGE CLASSROOM: A CASE STUDY AT AN ELEMENTARY SCHOOL IN BANDUNG - Choirunnisa, Jihan; Rodliyah, Rojab Siti (STKIP Persada Khatulistiwa Sintang, 2025)
This qualitative case study explores how cooperative learning unfolded during the implementation of Index Card Match (ICM) in a sixth-grade English as a Foreign Language (EFL) classroom in Bandung, Indonesia. Grounded in Johnson and Johnson’s cooperative learning theory, Vygotsky’s sociocultural framework, and Silberman’s active learning principles, the study focused on how small-group interaction fostered students’ social development through social mediation and collaborative behaviors. Twenty-five students participated in six ICM sessions, working in five small groups. Data were collected through observation sheets, field notes, and semi-structured interviews, and analyzed thematically using Saldaña’s coding framework Six interconnected themes emerged: (1) peer mediation and verbal scaffolding, (2) collaborative role negotiation, (3) self and peer regulation in task engagement, (4) clarification and meaning-making, (5) positive emotional climate and motivation, and (6) challenges and resolution in cooperative learning. These patterns reflected how students shared responsibilities, supported one another, and co-constructed understanding through dialogic interaction. The findings highlight that structured cooperative tasks like ICM can nurture students’ interpersonal growth and classroom social norms. This study offers insights for EFL educators seeking to promote meaningful peer collaboration in primary-level language classrooms.